(untitled) (Journal of Applied Learning and Teaching, 2023)
By increasing technology trend awareness, individuals can leverage novel and ground-breaking technologies to complete mundane activities and buy time to focus on other projects. This article presents an overview of why there is a slow pace of digital transformation in education in Ghana using ChatGPT (an advanced chatbot) as a case scenario. In this two-phase study, which used a triangulation approach (an exploratory sequential design), we found that most of the authors of publications about ChatGPT were not from the African continent or were affiliated with international institutions. A thematic analysis of interview data involving 34 academics in Ghana about ChatGPT revealed that most academics had limited knowledge about ChatGPT and artificial intelligence-powered chatbots. The main themes generated comprised the purpose of ChatGPT and chatbots, their usability and accuracy, and ChatGPT and artificial intelligence (AI) enthusiasm. The quantitative phase of the study surveyed the views of 50 academics who confirmed the minimal awareness of ChatGPT by Ghanaian academics. There were mixed views about the relevance and usefulness of ChatGPT in work-related tasks. Following the findings, we provide ways to create technology trend awareness for academics from African countries like Ghana to transition from being “laggards” to “early adopters”, as explained by Rogers’ diffusion of innovation theory. The findings call for policymakers and educators to promote technological awareness.